Haemanthamine alters sodium butyrate-induced histone acetylation, p21WAF1/Cip1 expression, Chk1 and Chk2 activation and leads to increased growth inhibition and death in A2780 ovarian cancer cells - Seifrtová, Martina; Havelek, Radim; Cahlíková, Lucie; Hulcová, Daniela; Mazánková, Naděžda; Řezáčová, Martina (Phytomedicine, 2017)
BACKGROUND: Haemanthamine (HA) and sodium butyrate (NaB) are promising candidates for chemotherapy as a treatment for cancer. PURPOSE: We aimed to determine the anticancer potential of HA and NaB, alone and in combination, in A2780 ovarian cancer cells and concurrently investigated anticancer potential in contrast to non-cancer human MRC-5 fibroblasts. METHODS: Antiproliferative effects were determined by WST-1 assay and by Trypan blue exclusion staining. Cell cycle distributions were studied by flow cytometry and protein levels were determined by Western blotting. RESULTS: The combination of HA and NaB caused a significant decrease in the proliferation of A2780 cells compared to the stand-alone treatment of cells by HA or NaB. This effect was less pronounced in non-cancer MRC-5 fibroblasts. In the later intervals, the number of A2780 living cells was strongly decreased by treatment using a combination of NaB and HA. This simultaneous application had no considerable effect in MRC-5 fibroblasts. The combination of NaB and HA led to the suppression of cells in the G1 phase and caused an accumulation of cells in the S and G2 phase in comparison to those treated with NaB and HA alone. Treatment of cells with NaB alone led to the activation of proteins regulating the cell cycle. Notably, p21WAF1/Cip1 was upregulated in both A2780 and MRC-5 cells, while checkpoint kinases 1 and 2 were activated via phosphorylation only in A2780 cells. Unexpectedly, NaB in combination with HA suppressed the phosphorylation of Chk2 on threonine 68 and Chk1 on serine 345 in A2780 cells and downregulated p21WAF1/Cip1 in both tested cell lines. The sensitization of cells to HA and NaB treatment seems to be accompanied by increased histone acetylation. NaB-induced acetylation of histone H3 and H4 and histone acetylation increased markedly when a combination of NaB and HA was applied. Whereas the most prominent hyperacetylation after HA and NaB treatment was observed in A2780 cells, the acetylation of histones occurred in both cell lines. CONCLUSION: In summary, we have demonstrated the enhanced activity of HA and NaB against A2780 cancer cells, while eliciting no such effect in non-cancer MRC-5 cells.
Keywords: Amaryllidaceae Alkaloids; Female; histony; fenantridiny; buněčný cyklus; Cell Cycle; Histones; Butyric Acid; inhibitor p21 cyklin-dependentní kinasy; checkpoint kinasa 2; Cyclin-Dependent Kinase Inhibitor p21; Ovarian Neoplasms; Checkpoint Kinase 1; Humans; fosforylace; checkpoint kinasa 1; nádory vaječníků; aktivace transkripce; Checkpoint Kinase 2; Acetylation; buněčné dělení; acetylace; lidé; Cell Line, Tumor; kyselina máselná; Phosphorylation; Cell Division; Phenanthridines; Transcriptional Activation; alkaloidy amarylkovitých; ženské pohlaví; nádorové buněčné linie